GROWTH, INSTABILITY AND ACREAGE RESPONSE FUNCTION IN PRODUCTION OF CUMIN IN RAJASTHAN - VANPAL KUMAR BOYAL,; D. C. PANT,; JAYA MEHRA, (The Bioscan, 2015)
The study was conducted to find out the compound growth rates, instability and acreage response functions of cumin crop in selected districts and for the state as a whole for the period I (1991-92 to 2000- 01), period II (2001- 02 to 2010-11) and overall period (1991-92 to 2010-11).The production of coriander crop increased significantly in Kota (6.18per cent), Jhalawar (9.65per cent), Baran (11.10per cent) districts and state as a whole (9.10per cent) and Production of cumin spice decreased in Jalore district (-7.66per cent), Jodhpur district (-7.78per cent) and state as a whole (-1.03per cent) during period I which was due to negative growth in productivity under the crop by (-) 2.16,(-) 12.68 and (-) 3.19 per cent per annum similarly, Production of fenugreek crop increased significantly in Kota (64.50per cent) and Jhunjhunu (36.22per cent) districts. The magnitude of instability in cumin crop was higher in production as compared to productivity and area except Barmer district (in context of I3 measure) during period I, where the variation in productivity was more. Cumin spice was found to have both pushing and pulling factors, almost equal in number. The lagged area and price, current and lagged year rainfall, current irrigated area and variability in yield responded in positive direction to boost up area under cumin.